Assessment of electrolyte imbalance among benign prostate hyperplasia patients in Western Kenya - Ongonga, Royronald; Menza, Nelson; Demba, Rodgers N. (International Journal of Research in Medical Sciences, 2023)
Background: Benign prostate hyperplasia (BPH) results in the enlargement of the gland and ultimately obstructs the bladder and the kidney. The effect on the kidney results in the dysregulation of the electrolyte causing electrolyte imbalance. Methods: An analytical cross-sectional study conducted at a tertiary teaching hospital aimed at assessing the levels and severity of electrolyte imbalance among BPH patients. The blood samples were analyzed for electrolytes and PSA levels for both patients and control group. An Independent t-test was used to compare the means of the BPH patients and healthy control subjects. Chi-square was used to determine the association between the electrolyte imbalance and the PSA levels of the BPH patients. Results: The mean age of the BPH patients and the healthy individuals was 65.47±12.55 and 64.52±12.19 years respectively. Hyponatremia, and hypernatremia were observed in 26.08% (n=104) and 4.22% (n=8) of the BPH patients respectively. There was a statistical significance positive correlation between potassium (K) and sodium (Na) concentrations (r=0.350, p<0.01), as well as a notable positive association between chloride (Cl) and magnesium (Mg) levels (r=0.288, p<0.01). PSA biomarker levels varied among the patients. There was a statistical significance (<0.0001*) difference in PSA levels between the BPH patients and the control group. Conclusions: With high prevalence of electrolyte imbalance among BPH patients there is a need to monitor the electrolytes and PSA levels in the management of BPH aiming at restoration of kidney function.